Seafloor observations indicate spatial separation of coseismic and postseismic slips in the 2011 Tohoku earthquake - Takeshi Iinuma (Nature Portfolio, 2016)
Postseismic slip of the 2011 Tohoku earthquake in Japan has occurred on the plate interface, but quantifying the slip has been difficult due to a lack of seafloor data. Here, the authors use seafloor and terrestrial data and show that areas of co- and postseismic slip are spatially separated.